Effect of Plasma Nitriding on the Creep and Tensile Properties of the Ti-6Al-4V Alloy - Gisele F. C. Almeida; Antônio A. Couto; Danieli A. P. Reis; Marcos Massi; Argemiro S. da Silva Sobrinho; Nelson B. de Lima (Metals, 2018)
This work aimed to enhance the creep resistance of Ti-6Al-4V alloy treated by plasma nitriding. The nitriding was performed on specimens with a Widmanstätten microstructure for four hours at 690 °C under a gas atmosphere containing Ar:N2:H2 (0.455:0.455:0.090). X-ray diffraction analysis showed that the ε-Ti2N and δ-TiN formed on the nitrided sample, in addition to the α-Ti and β-Ti matrix phases. The layer thickness of this sample was about 1 µm. Hot tensile tests were performed in the temperature range of 500 to 700 °C on nitrided and non-nitrided samples, which indicated an increased strength of the nitrided samples. The same temperature range was used for the creep tests in a stress range of 125 to 319 MPa. The plasma-nitrided samples exhibited better creep resistance when compared to the untreated samples. This result was demonstrated by the decreased secondary creep rate and the increased final creep time. This improvement in the creep resistance appeared to be associated with the formation of the nitrided layer, which worked as a barrier to oxygen diffusion into the material and due to the formation of a surface residual compressive stress.